2016
DOI: 10.1139/cjas-2015-0079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an exogenous enzyme-containing inoculant on fermentation characteristics of barley silage and on growth performance of feedlot steers

Abstract: This study investigated the effects of an inoculant on silage fermentation, aerobic stability, and the growing and finishing performance of feedlot steers. Whole-crop barley (Hordeum vulgare L.) was chopped, wilted [350-400 g kg −1 dry matter (DM)], and ensiled without (Control) or with (Treated) a bacterial inoculant containing a mixture of Pediococcus pentosaceus, Lactobacillus plantarum, and Propionibacterium freudenreicheii (1.3 × 105 CFU g −1 forage), as well as enzymes applied to fresh forage ensiled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…In studies that enable differentiation, the addition of fibrolytic enzymes to bacterial inoculants has had a positive effect on silage quality, increasing in saccosoluble NDF and improving feed efficiency in feedlot cattle (Zahiroddini et al, 2004). In other studies, less well-defined enzyme cocktails added in conjunction with a complex mixture of inoculants accelerated the post-ensiling decline in pH but failed to improve the growth performance of steers (Addah et al, 2016). Lynch et al (2015) added cellulase and xylanase to corn forage before ensiling alone and in combination with a ferulic acid esterase-producing (FAE) silage inoculant and found that the combination resulted in a lower pH and higher WSC than the control silage after 70 d of ensiling.…”
Section: Exogenous Enzymesmentioning
confidence: 99%
“…In studies that enable differentiation, the addition of fibrolytic enzymes to bacterial inoculants has had a positive effect on silage quality, increasing in saccosoluble NDF and improving feed efficiency in feedlot cattle (Zahiroddini et al, 2004). In other studies, less well-defined enzyme cocktails added in conjunction with a complex mixture of inoculants accelerated the post-ensiling decline in pH but failed to improve the growth performance of steers (Addah et al, 2016). Lynch et al (2015) added cellulase and xylanase to corn forage before ensiling alone and in combination with a ferulic acid esterase-producing (FAE) silage inoculant and found that the combination resulted in a lower pH and higher WSC than the control silage after 70 d of ensiling.…”
Section: Exogenous Enzymesmentioning
confidence: 99%
“…The inoculant used was BIOTAL PLUS II® (Lallemand Animal Nutrition, Milwaukee, Wisconsin) that contained viable cells of the LAB Pediococcus pentosaceus 12,455 (homofermentative) and Propionibacterium freudenreichii R2453 (heterofermentative) and specific enzymes, which were expected to enhance fiber hydrolysis during ensiling [5]. The inoculant was applied following instructions; hence, it was expected to supply 100,000 CFU/gram of forage.…”
Section: Methodsmentioning
confidence: 99%
“…Technical alternatives for ensiling alfalfa forage are to harvest in afternoon hours [3], wilting [4] and the use of lactic acid bacteria (LAB) homo-and heterofermentative inoculants with enzymes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Al considerar el tiempo de muestreo de manera específica, se observó que a los 30 días el pH disminuyó en comparación con los resultados obtenidos a los 15 días, esto se debe posiblemente a la producción de ácido láctico por parte de microorganismos homofermentadores como Lactobacillus plantarum (Filya, 2003ay Addah et al, 2016 aspecto que refleja un adecuado proceso de ensilado (Jaimes et al, 2009). Resultados similares son reportados por la literatura (Filya, 2003b;Jalč et al, 2009;Corral-Luna et al, 2011;Addah et al, 2011;Addah et al, 2016;Joo et al, 2018).…”
Section: Phunclassified